N-heterocyclic carbene-catalyzed cross-coupling of aromatic aldehydes with activated alkyl halides - Padmanaban, Mohan; Biju, Akkattu T.; Glorius, Frank (Organic Letters, 2011)
N-Heterocyclic carbene-catalyzed umpolung of aldehydes followed by their interception with diarylbromomethanes has been reported. This conceptually novel transition-metal-free cross-coupling of aldehydes with alkyl halides works well at low catalyst loadings and under mild reaction conditions leading to the formation of diaryl acetophenone derivatives in good yields. In addition, α-halo ketones and esters can also be used as aldehyde reaction partners.